ANALISIS USAHATANI KANGKUNG (Ipomoea aquatica Forsk) DI DESA KAIMA KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Pedro R. P. Hutahaean; Mex L. Sondakh; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2017)
This study aims to analyze how the income of water spinach farmers (Ipomoea aquatica Forsk). This research was conducted in Kaima Village, Kauditan District, North MinahasaRegency and lasted from April 2016 until October 2017. The research method used in this research is survey method by interview all farmers of kangkung. Data collection method in this research is to use primary data through prepared list of questions that are obtained through direct interviews with farmers and secondary data from related agencies such as Head of Village Office, Statistic and Agricultural Extension Offices. Sampling method is the determination of saturated samples means that all water spinach farmers are used as a sample much as 6 respondents. The concept of measurement of variables in this study is the production, land area, selling price, revenue, expenditure, and supporting variables. Analysis of data used is the data obtained are presented in table form and analyzed descriptively. The results showed that the income of kangkung farming in Kaima Village, Kecamatan.Kauditan was beneficial.